Analysis of Surface Microdefects Localization Possibilities - Bulbenkienė, V.; Pūras, R.; Sakalauskas, S. (Elektronika ir Elektrotechnika, 2006)
Analysis of linear spatial resolution of vibrating Kelvin–Zisman electrode is carried out in case when the size of defective area is substantially less than diameter of vibrating probe. Dependence of relative error of voltage determination and defective area center’s coordinate determination on scanning speed was examined and influence of measuring device pass band was estimated also. Analysis of theoretical results and carried out experiments on real samples and its models allows us to state that contactless capacitic electric potential measuring devices operating on principle of vibrating Kelvin Zisman probe allows to localize single microdefects and its groups when their dimensions are less the diameter of vibrating probe, approximately measure surface electric potential and electron work function of these microdefective areas. Ill. 5, bibl. 7 (in English; summaries in English, Russian and Lithuanian).